Interlanguage and Intralanguage Errors in Speaking Video Project of Language Major of Senior High School Students in Singaraja, North Bali - Putu Dita Marantika (Universitas Pendidikan Ganesha, 2024)
This study analyze and identified interlanguage and intralanguage form of error found on senior high school students on their speaking video project. This study was design in qualitative research approach which is the document analysis is used during the data analysis. The data were collected through the video project by senior high school students in SMAN 1 Singaraja especially Bahasa major. The result show that Interlanguage forms that appear such as omission, addition, misformation. The intralanguage forms found overgeneralization (ed/d) & (suffix –s), induce error, error of over production, error of avoidance (mispronounce). According to the findings of this study, children faced interlanguage and intralanguage forms while learning a English especially speaking. Teachers and tutors can use appropriate strategies and materials to help students learn more effectively. Furthermore, this study can help us prepare for future research on various subjects and references for applied linguistics courses.